2021
DOI: 10.3390/jcm10173865
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI Evaluation of Oropharyngeal Squamous Cell Carcinoma. A Mono-Institutional Study

Abstract: The aim of this paper is to define the pre-treatment radiological characteristics of oropharyngeal squamous cell carcinoma (OPSCC) using morphological and non-morphological magnetic resonance imaging (MRI), based on HPV status, in a single-institution cohort. In total, 100 patients affected by OPSCC were prospectively enrolled in the present study. All patients underwent 1.5T MR with standard sequences, including diffusion-weighted imaging with and intravoxel incoherent motion (IVIM-DWI) technique and a dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 45 publications
1
36
1
Order By: Relevance
“…We found that the ADC and all NG-IVIM parameters were related to HPV status. HPV-negative patients had a higher ADC and NG-IVIM parameter D than HPV-positive patients, which is in line with existing literature [4] , [9] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . Since HPV-negative patients in general have a worse response to treatment than HPV-positive patients, that finding by itself would suggest that a high ADC is related to a poorer response, which has been reported also before in studies about pre-treatment DWI that did not correct for HPV status [1] , [32] , [33] .…”
Section: Discussionsupporting
confidence: 91%
“…We found that the ADC and all NG-IVIM parameters were related to HPV status. HPV-negative patients had a higher ADC and NG-IVIM parameter D than HPV-positive patients, which is in line with existing literature [4] , [9] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . Since HPV-negative patients in general have a worse response to treatment than HPV-positive patients, that finding by itself would suggest that a high ADC is related to a poorer response, which has been reported also before in studies about pre-treatment DWI that did not correct for HPV status [1] , [32] , [33] .…”
Section: Discussionsupporting
confidence: 91%
“…Twenty-one studies had a retrospective cohort study design [2,[19][20][21][22]25,26,28,29,31,32,35,[37][38][39]42,44,45,[47][48][49], and seven studies had a prospective cohort study design [23,27,40,41,43,46,50]. Of the twentyeight included papers, five papers focused on structural MRI sequences that were used in routine clinical examinations [19][20][21][22][23], nineteen focused on DWI sequences [2,25,[27][28][29]31,32,35,36,38,39,41,42,[44][45][46][47]...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eleven studies used 1.5T MRI scanners [19,25,27,28,38,43,[45][46][47]49,50], nine studies used 3.0T MRI scanners [20,22,26,29,32,37,40,41,44], and eight studies used a combination of 1.5T and 3.0T MRI scanners [2,21,23,31,35,39,42,48]. Of the twenty-eight studies, nineteen investigated OPSCC exclusively [19][20][21][22][23]27,29,31,32,37,38,40,42,[44][45][46][47][48][49], three studies investigated oral cavity (OC)SCC as well as OPSCC [2,26,28], and ...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Lower ADC and tissue diffusion coefficient (D t ) values have been observed in primary tumours and metastatic lymph nodes of patients with HPV+ OPC, with D t values achieving good levels of sensitivity (85.7–94.9%) and specificity (61.9–64.7%) when combined with risk factors, such as smoking and alcohol intake. 60,67 However, perfusion-related parameters, including the perfusion fraction (f) and perfusion-related diffusion coefficient (D*), have not been found to be discriminatory. 67 Due to the paucity of data and time consuming nature of the IVIM sequence, its use remains primarily in the research domain.…”
Section: Structural Imaging With Ct and Mrimentioning
confidence: 99%
“… 70 However, a more recent study found no difference in DCE parameters between HPV+ and HPV- OPC. 60 Given the inconsistencies, further data are required before it can be relied upon to aid prediction of HPV status.…”
Section: Structural Imaging With Ct and Mrimentioning
confidence: 99%